2019
DOI: 10.1021/acs.inorgchem.9b01952
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Lanthanide-Containing Polyoxotantalate Clusters with Efficient Photoluminescence Properties

Abstract: Eight novel lanthanide-containing polyoxotantalates, Cs3[Ln­(H2O)6{H4(TaO2)6As4O24}]·7H2O (Ln = Sm (1), Eu (2), Tb (3), Dy (4), Er (5), Tm (6), Yb (7), Lu (8)), have been obtained via a one-pot reaction methodology. Each of these compounds is made up of the new type polyanion [(TaO2)6As4O24]10– with Ln3+ linkers, giving a one-dimensional chain. The compounds represent the first family of “pure” Ta-based polyoxometalate lanthanide derivatives. These architectures were characterized by various physicochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19] In recent decades, lots of Ln-POM derivatives with attractive structures and novel physical and chemical properties have been reported. Nevertheless, most of these studies focus solely on the photoluminescence (PL) properties of Ln-POM derivatives, [20][21][22][23][24][25][26][27][28] although there are a few examples demonstrating SMM behaviors. [29][30][31][32][33][34] It is becoming widely accepted that the coordination environment of the Ln center has a great influence on the dynamic relaxation processes of Ln-SMMs.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19] In recent decades, lots of Ln-POM derivatives with attractive structures and novel physical and chemical properties have been reported. Nevertheless, most of these studies focus solely on the photoluminescence (PL) properties of Ln-POM derivatives, [20][21][22][23][24][25][26][27][28] although there are a few examples demonstrating SMM behaviors. [29][30][31][32][33][34] It is becoming widely accepted that the coordination environment of the Ln center has a great influence on the dynamic relaxation processes of Ln-SMMs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a unique Co-containing POTa was reported, where four Lindqvist units are joined to form an aggregate via eight Co 2+ cations . POTas were also successfully prepared with d-block metal cations (M n + ) including Rh 2+ , Ru 2+ , Ir 2+ , Re + , Mn + , Cu 2+ , Ti 4+ , Co 2+ , and Ni 2+ ,,− or lanthanide cations . But only in a few structures, the M n + cations expand the {Ta 6 O 19 } moiety via M–O covalent bonds such as in {[Cu­[1,3-dap) 2 ] 2 [Cu­(1,3-dap)­(H 2 O)] 2 [Ta 6 O 19 ]}·8H 2 O, {[Cu­(en) 2 ] 4 [Ta 6 O 19 ]}·14H 2 O, H 2 {[Cu­(en) 2 ] 3 [Cu­(en)­(H 2 O) 2 Cu­(en)­(Ta 6 O 19 )] 2 }·30H 2 O, Na 4 K 6 [(Ta 6 O 19 )­Co­(en) 2 ]·30H 2 O, and K 2 [Ni­(dien) 2 ]­{[Ni­(dien)] 2 Ta 6 O 19 }·11H 2 O. ,, The few rare examples presented here indicate that integration or covalent expansion of POTas by M n + cations is a challenge, which may be at least partially explained by the high pH value required for product formation, leading possibly to M hydroxides.…”
Section: Introductionmentioning
confidence: 99%
“…10 POTas were also successfully prepared with d-block metal cations (M n+ ) including Rh 2+ , Ru 2+ , Ir 2+ , Re + , Mn + , Cu 2+ , Ti 4+ , Co 2+ , and Ni 2+10,28,33−37 or lanthanide cations. 38 But only in a few structures, the M n+ cations expand the {Ta 6 partially explained by the high pH value required for product formation, leading possibly to M hydroxides. But in the last years, it has been shown that the integration of different and advanced cations in POMs is of essential importance when it comes to structural design, specification, and properties of the material.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Especially, Eubased complexes are the most widely studied because of the sensitivity to the coordination environment, narrow bandwidth, high fluorescence intensity and long lifetime. [22][23][24][25] Meantime, because of the difficulty of directly exciting Ln 3 + ions, so it is necessary to introduce ligands, such as POMs, which can overcome the low molar absorption coefficient caused by the 4f-4f transition of Laporte, and sensitize the emission center of Ln 3 + ions through LMCT mediated intramolecular energy transfer. [26] Furthermore, in order to enhance the temperature sensing performance of the rare earth ion complexes, nonfluorescent rare earth ions (La 3 + , Gd 3 + ) are doped into the luminescent rare earth complexes to obtain better temperature sensing performance.…”
Section: Introductionmentioning
confidence: 99%